Smarginare il corpo: il processo di scrittura e la costituzione d’identità - Lattanzi, Emma (Mechane, 2024)
This essay focuses on the relationship between writing and identity. First, it analyzes certain premises that, if left unchallenged, could lead to dogmatic positions. Elevating Derrida’s exercise of suspicion to an operational method, it questions the centrality of oral language, the binary opposition between reason-desire and representationalism. Consequently, the writing process is understood from the perspective of a desiring, embodied and situated subject, based on a synthesis of Butler, Merleau-Ponty and Sartre’s ideas. Far from being merely a tool of disembodied reason, writing is one of the ways that specifically describe Homo sapiens’ way of being in the world. Writing shapes human beings and the environment they inhabit within a continuously open and generative horizon of meaning.